Muon studies of spin dynamics in polyaniline - Pratt, F; Ishida, K; Nagamine, K; Pattenden, P; Jestadt, T; Chow, K; Blundell, S; Hayes, W; Monkman, A (1997)
The muon is a valuable probe of spin excitations in polymers, as the muon implantation process itself generates a lest excitation whose dynamical properties can be studied via the evolution of the muon spin polarisation. We report here studies on undoped polyaniline in its emeraldine base form (PANI:EB). Characteristic field dependences and cutoff frequencies for the muon spin relaxation are observed which are related to the spin diffusion. One-dimensional diffusion is seen at low temperatures and at short probe times. The on chain diffusion is observed to have a weak metallic temperature dependence whereas the interchain diffusion is strongly activated and phenyl ring rotations are seen to have an important effect on the diffusion processes.